Forces applied during classical touch assays for Caenorhabditis elegans. - Adam L Nekimken (PLoS ONE, 2017)
For decades, Caenorhabditis elegans roundworms have been used to study the sense of touch, and this work has been facilitated by a simple behavioral assay for touch sensation. To perform this classical assay, an experimenter uses an eyebrow hair to gently touch a moving worm and observes whether or not the worm reverses direction. We used two experimental approaches to determine the manner and moment of contact between the eyebrow hair tool and freely moving animals and the forces delivered by the classical assay. Using high-speed video (2500 frames/second), we found that typical stimulus delivery events include a brief moment when the hair is contact with the worm's body and not the agar substrate. To measure the applied forces, we measured forces generated by volunteers mimicking the classical touch assay by touching a calibrated microcantilever. The mean (61 μN) and median forces (26 μN) were more than ten times higher than the 2-μN force known to saturate the probability of evoking a reversal in adult C. elegans. We also considered the eyebrow hairs as an additional source of variation. The stiffness of the sampled eyebrow hairs varied between 0.07 and 0.41 N/m and was correlated with the free length of hair. Collectively, this work establishes that the classical touch assay applies enough force to saturate the probability of evoking reversals in adult C. elegans in spite of its variability among trials and experimenters and that increasing the free length of the hair can decrease the applied force.